Odpowiedzi

2010-03-03T20:36:10+01:00
A) (3/5m² + 2/3n² + 6) + ( -1/3m² - 2/3n² - 2 3/5)=
3/5m^+2/3n^+6-1/3m^-2/3n^-2 3/5=
=9/15m^-5/15m^+4 2/5=
=4/15m^+4 2/5

b) (0,5xy² - 1,2y² + 5) + ( -0,8y² - 2,5xy² - 2 1/8 )=
=0,5xy^-1,2y^+5-0,8y^-2,5xy^-2 1/8=
-2xy^-2y^+2 7/8
2010-03-03T20:37:48+01:00
A) 3/5m² + 2/3n²+6- 1/3m²-2/3n²-2 3/5=3/5m²-1/3m²-2 3/5=
9/15m²-5/15m²-2 3/5= 4/15m²- 2 3/5
b)0,5xy² - 1,2y² + 5 -0,8y² - 2,5xy² - 2 1/8= - 2 xy²-2y²+2 7/8
2010-03-03T20:38:13+01:00
A) (3/5m² + 2/3n² + 6) + ( -1/3m² - 2/3n² - 2 3/5)=3/5m² + 2/3n² + 6-1/3m² - 2/3n² - 2 3/5=9/15m²-5/15m²+6-13/5=4/15m²+17/5

b) (0,5xy² - 1,2y² + 5) + ( -0,8y² - 2,5xy² - 2 1/8 )=0,5xy² - 1,2y² + 5-0,8y² - 2,5xy² - 2 1/8=1/2xy²-12/10y²+5-8/10y²-25/10xy²-17/8=-20/10xy²-20/10y²+23/8=-2xy²-2y²+23/8